2022
DOI: 10.1158/2326-6066.cir-21-0146
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC Mutagenesis Inhibits Breast Cancer Growth through Induction of T cell–Mediated Antitumor Immune Responses

Abstract: The APOBEC family of cytidine deaminases is one of the most common endogenous sources of mutations in human cancer. Genomic studies of tumors have found that APOBEC mutational signatures are enriched in the HER2 subtype of breast cancer and are associated with immunotherapy response in diverse cancer types. However, the direct consequences of APOBEC mutagenesis on the tumor immune microenvironment have not been thoroughly investigated. To address this, we developed syngeneic murine mammary tumor models with in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…However, the role of APOBECs in cancers remains ambiguous. For example, it is reported that APOBEC mutagenesis could drive tumor evolution in metastatic thoracic tumor and HPV-driven tumor but inhibit breast cancer growth through immune activation 12 , 53 , 54 . When it comes to APOBEC3B, it is the most widely investigated member of APOBEC family and causes a variety of mutagenic outcomes 55 , but its biological impact on cancers still remains unclear, even contrary.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of APOBECs in cancers remains ambiguous. For example, it is reported that APOBEC mutagenesis could drive tumor evolution in metastatic thoracic tumor and HPV-driven tumor but inhibit breast cancer growth through immune activation 12 , 53 , 54 . When it comes to APOBEC3B, it is the most widely investigated member of APOBEC family and causes a variety of mutagenic outcomes 55 , but its biological impact on cancers still remains unclear, even contrary.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the relationships between the mutational signatures and immunity were studied in LUSC [11,12], which showed that the APOBEC signature was associated with the immune response. Furthermore, recently, the relationship between APOBEC mutagenesis and the immune response in breast cancer has been reported [50], and some studies have shown an association between APOBEC mutagenesis and immunity in HNSC [51,52]. In my experimental results, the APOBEC signatures were also observed as the highest coefficients in BRCA, HNSC, as well as LUSC.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, while, APOBEC1 possesses DNA demethylase activity ( 48 50 ), APOBEC mutagenesis influencing the tumor evolution in ER+/HER2-breast cancer has been reported ( 51 ). Most recently it was shown that the APOBEC mutagenesis prohibited the growth of breast tumors by eliciting immunogenic responses ( 52 ).…”
Section: Epigenetic Players In Breast Cancermentioning
confidence: 99%